2017
DOI: 10.1071/rdv29n1ab47
|View full text |Cite
|
Sign up to set email alerts
|

47 Cryopreservation of Bovine Germ Cell Using Antifreeze Polyamino-Acid (Carboxylated Poly-L-Lysine)

Abstract: Carboxylated poly-l-lysine (CPLL) is an ampholytic polymer compound, and it is obtained by converting 65% amino groups to carboxyl groups after synthesising ε-poly-l-lysine aqueous solution and succinic anhydride. CPLL has cryoprotective property similar to antifreeze protein, and addition of CPLL into cryopreservation medium improves the post-thaw survival rate of cells and embryos. In this research, we examined the effectiveness of CPLL as a bovine germ cell cryoprotective material. In experiment 1 (in sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The addition of 3.25% (v/v) glycerol along with 0.5% (w/v) carboxylated poly L-Lysine (CPLL) in Japanese black bull semen improved sperm plasma membrane and fertility. The addition of CPLL in cryopreservation medium improves sperm cells survival due to its cryoprotective property and results in improved conception rates (Fujikawa et al, 2017) According to our knowledge, no work has been reported on addition of L-lysine in buffalo bull semen in terms of post-thaw quality. This study aimed to evaluate post-thaw semen quality parameters, antioxidant enzymatic activity and oxidative stress after addition of various concentrations of L-lysine in Nili-Ravi buffalo bull semen during cryopreservation.…”
Section: Introductionmentioning
confidence: 97%
“…The addition of 3.25% (v/v) glycerol along with 0.5% (w/v) carboxylated poly L-Lysine (CPLL) in Japanese black bull semen improved sperm plasma membrane and fertility. The addition of CPLL in cryopreservation medium improves sperm cells survival due to its cryoprotective property and results in improved conception rates (Fujikawa et al, 2017) According to our knowledge, no work has been reported on addition of L-lysine in buffalo bull semen in terms of post-thaw quality. This study aimed to evaluate post-thaw semen quality parameters, antioxidant enzymatic activity and oxidative stress after addition of various concentrations of L-lysine in Nili-Ravi buffalo bull semen during cryopreservation.…”
Section: Introductionmentioning
confidence: 97%
“…The addition of 3.25% (v/v) glycerol along with 0.5% (w/v) carboxylated poly L-Lysine (CPLL) in Japanese black bull semen improved sperm plasma membrane and fertility. The addition of CPLL in cryopreservation medium improves sperm cells survival due to its cryoprotective property and results in improved conception rates (Fujikawa et al, 2017) According to our knowledge, no work has been reported on addition of L-lysine in buffalo bull semen in terms of post-thaw quality. This study aimed to evaluate post-thaw semen quality parameters, antioxidant enzymatic activity and oxidative stress after addition of various concentrations of L-lysine in Nili-Ravi buffalo bull semen during cryopreservation.…”
Section: Introductionmentioning
confidence: 97%